Effect of occupational therapy on the occurrence of delirium in critically ill patients: a systematic review and meta-analysis - Zhao, Jun; Fan, Kaipeng; Zheng, Suqin; Xie, Guangyao; Niu, Xuekang; Pang, Jinkuo; Zhang, Huihuang; Wu, Xin; Qu, Jiayang (Frontiers in Neurology, 2024)
Aim Delirium poses a major challenge to global health care, yet there is currently a dearth of single effective interventions or medications. Particularly, addressing delirium induced by critical illness is a complex process. Occupational therapy is considered to have a high potential for use in the prevention of delirium, as it involves both cognitive training and training in ADL. To comprehensively analyze the effect of occupational therapy on delirium prevention, we evaluated the effects of occupational therapy vs. standard non-pharmacological prevention on incidence and duration of delirium, clinical outcomes and rehabilitation outcomes in critically ill patients. Methods The data sources, including PubMed/Medline, Web of Science, EMBASE, and Cochrane Library, were comprehensively searched from their inception until 15 October 2023. Following the PICOS principle, a systematic screening of literature was conducted to identify relevant studies. Subsequently, the quality assessment was performed to evaluate the risk of bias in the included literature. Finally, outcome measures from each study were extracted and comprehensive analysis was conducted using Review Manager 5.4. Results A total of four clinical trials met the selection criteria. The pooled analysis indicated no significant difference in the incidence and duration of delirium between the OT group and standard non-pharmacological interventions. A comprehensive analysis of clinical outcomes revealed that OT did not significantly reduce the length of hospital stay or ICU stay. Meanwhile, there was no significant difference in mortality rates between the two groups. It is noteworthy that although grip strength levels did not exhibit significant improvement following OT intervention, there were obvious enhancements observed in ADL and MMSE scores. Conclusion Although occupational therapy may not be the most effective in preventing delirium, it has been shown to significantly improve ADL and cognitive function among critically ill patients. Therefore, we contend that occupational therapy is a valuable component of a comprehensive multidisciplinary approach to managing delirium. In the future, high-quality researches are warranted to optimize the implementation of occupational therapy interventions for delirium prevention and further enhance their benefits for patients.